Implementasi Metode SDLC Waterfall Untuk Rancang Bangun Sistem Informasi Pengaduan Masyarakat Berbasis Web Dengan Notifikasi Telegram (Studi Kasus : Kelurahan Bojongsari Baru, Kota Depok) - Rendi Agum Pratama; Teti Desyani (OKTAL : Jurnal Ilmu Komputer dan Sains, 2024)
The development of information technology has progressed from time to time. Demand that each individual or group must keep up with the times so as not to be left behind. One of them is the Bojongsari Baru Village, which is a village government institution in the city of Depok, which really needs a fast, practical and structured information service system to serve its citizens. The information service system that runs in the Bojongsari Baru Village is still running manually, especially in terms of public complaints. The community still comes directly to the kelurahan to report complaints, it is not certain that the complaints submitted are immediately responded to by the lurah or kelurahan officials, because they are not present, so this service is not fast, practical and structured. Based on these problems, this study aims to design a web-based public complaint system with real-time telegram notification features for Bojongsari Baru Village. By implementing the SDLC Waterfall method which consists of needs analysis, design, programming, system testing, and maintenance. The results of this study aim for both parties to obtain information and means of communication quickly, making it easier for people who want to submit complaints easily without having to come to the village and assist the village in handling complaints and managing information data.